PENGARUH STRUKTUR KEPEMILIKAN DAN RASIO KEUANGAN TERHADAP HARGA SAHAM - Natasha Olivia The; Yuniarwati Yuniarwati (Jurnal Paradigma Akuntansi, 2022)
The purpose of this study is to empirically examine the effect of managerial ownership, institutional ownership, dividend payout ratio, and debt to equity ratio on stock prices. The subjects of this research are the basic industry and chemical sectors listed on the Indonesia Stock Exchange (IDX) for the year 2017-2019. The sampling technique used was purposive sampling, with data samples obtained from are 54 companies. The data processing technique used is multiple regression analysis assisted by Microsoft Excel 2019 and the EViews version 11 program. The results of this study indicate that managerial ownership, institutional ownership, and debt to equity payment ratios have no significant effect on stock prices, while the dividend payout ratio have a positive and significant effect on stock prices. The implication of this research is the need to increase the proportion of managerial ownership and increase the monitoring function of institutional ownership so that the company's stock price also increases. Besides, adding other indicators for investors to assess the financial health and share price of a company.